Synthesis of (+/-) debenzoyl analogs of norsampsones as potential anticancer agents - Jadhav, Amol R.; Thombal, Raju S.; Nigam, Preeti; Jadhav, Vrushali H. (Tetrahedron Letters, 2015)
Synthesis of (+/-) debenzoyl analogs of norsampsones 1 and 2 is reported starting from commercially available 1,3-cyclohexadione in six steps with overall yields of 37% and 36%, respectively. Compounds 1 and 2 were tested for their anticancer activity and showed moderate anticancer activity against HeLa cell lines. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Acylphloroglucinols; Anticancer; Debenzoyl; Norsampsones